Exploring The Relationship Between Power System And Its Automation And Relay Protection - Shen, Yuyin (Journal of Theory and Practice of Engineering Science, 2023)
The construction of power system projects plays an important role in the contemporary socio-economic development of China, which can meet people's daily electricity needs while promoting the stability of system operation. At present, China has begun to integrate automation technology into the construction of the power system and improve the rationality of power resource transmission through relay protection mechanisms. When applying relay protection in practice, it is necessary to take the relationship between the power system and its automation and relay protection as a prerequisite, so that it can play a substantive role. The article mainly discusses the practical application of relay protection by analyzing the characteristics of power systems and their automation and their relationship with relay protection.